The Relation of Complete Blood Count Parameters with Metabolic and Clinical Parameters in Overweight and Obese Children - Ayşe Anık; Elif Çelik; Ahmet Anık (Galenos Yayinevi, 2021)
Aim:This study aims to assess white blood cell count, platelet count, and platelet indices as a metabolic indicator in overweight, obese and morbidly obese children.Materials and Methods:One-hundred and thirty overweight, 341 obese, 188 morbidly obese children and 110 controls were enrolled in the study. Anthropometric measurements, pubertal status, complete blood count parameters [white blood cells (WBC), platelet, mean platelet volume (MPV), plateletcrit (PCT), and platelet distribution width (PDW)], WBC differential (neutrophils, lymphocytes, and monocytes), neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR), and serum levels of glucose, lipids, aspartate transaminase (AST), and alanine transaminase (ALT), insulin and thyroid hormones were obtained from the hospital records. Insulin resistance was assessed according to the homeostasis model assessment-insulin resistance (HOMA-IR) index.Results:WBC, neutrophil, lymphocyte, and monocyte counts were highest in the morbidly obese group followed by the obese, overweight, and healthy groups, respectively. Platelet count, PCT, and PDW were significantly higher in the morbidly obese, obese, and overweight groups compared to the healthy group. However, there was no significant difference between the groups in terms of MPV, NLR, and PLR. WBC, neutrophil, lymphocyte, platelet, PCT, ALT, and triglyceride levels were higher in children with insulin resistance than those without insulin resistance. There was a positive correlation with the neutrophil, lymphocyte, monocyte count, and PCT value, and a negative correlation with the PDW value. Moreover, there was a positive correlation between the HOMA-IR and WBC, neutrophil, lymphocyte count, and PCT.Conclusion:WBC, neutrophils, lymphocytes, monocytes, platelets, and PCT values increase in childhood obesity, which could point towards low-grade chronic inflammation and this increase in WBC, neutrophils, lymphocytes, and PCT value may be associated with insulin resistance.